Adhesion-clutch between DCC and netrin-1 mediates netrin-1–induced axonal haptotaxis - Qiu, Zhen; Minegishi, Takunori; Aoki, Daichi; Abe, Kouki; Baba, Kentarou; Inagaki, Naoyuki (Frontiers in Molecular Neuroscience, 2024)
The growth cone, a motile structure located at the tip of growing axons, senses extracellular guidance cues and translates them into directional forces that drive axon outgrowth and guidance. Axon guidance directed by chemical cues on the extracellular adhesive substrate is termed haptotaxis. Recent studies reported that netrin-1 on the substrate functions as a haptotactic axon guidance cue. However, the mechanism mediating netrin-1–induced axonal haptotaxis remains unclear. Here, we demonstrate that substrate-bound netrin-1 induces axonal haptotaxis by facilitating physical interactions between the netrin-1 receptor, DCC, and the adhesive substrates. DCC serves as an adhesion receptor for netrin-1. The clutch-linker molecule shootin1a interacted with DCC, linking it to actin filament retrograde flow at the growth cone. Speckle imaging analyses showed that DCC underwent either grip (stop) or retrograde slip on the adhesive substrate. The grip state was more prevalent on netrin-1–coated substrate compared to the control substrate polylysine, thereby transmitting larger traction force on the netrin-1–coated substrate. Furthermore, disruption of the linkage between actin filament retrograde flow and DCC by shootin1 knockout impaired netrin-1–induced axonal haptotaxis. These results suggest that the directional force for netrin-1–induced haptotaxis is exerted on the substrates through the adhesion-clutch between DCC and netrin-1 which occurs asymmetrically within the growth cone.